Penerapan Model Pembelajaran STEM dalam Meningkatkan Pemahaman Siswa terhadap Sistem Pernafasan - Fitri Khoirunnisa; Gina Tsania; Indah Permatasari Putri; Iwan Ridwan Yusuf (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Attractive teaching methods and materials in the 21st century are very necessary to increase students' active role and interest in learning. One approach that has been integrated is the STEM (Science, Technology, Engineering, and Mathematics) learning model. This research aims to analyze the effectiveness of implementing a STEM learning model based on Project-Based Learning (PjBL) in increasing students' understanding of the human respiratory system. The research method used was experimental, with practicum related to the dangers of smoking as part of the learning implementation. The research subjects involved 23 grade 8 students at SMP Muhammadiyah 10 Bandung. The experimental class was given PjBL-based STEM learning with an interactive practicum approach. The research results showed a significant increase in understanding in the experimental class based on pretest and posttest analysis using statistical tests. This research reveals that this approach is effective in increasing student engagement, facilitating holistic understanding of concepts, and motivating students to think critically about the negative impacts of smoking on the respiratory system. Hands-on experimental activities also strengthen the connection between theory and practice. Thus, the application of the PjBL-based STEM learning model through practicum on the dangers of smoking has proven to be effective in increasing students' understanding of the respiratory system. This research recommends using a similar model in the curriculum to optimize student learning outcomes, especially in the field of science.